Health system challenges and opportunities in organizing non-communicable diseases services delivery at primary healthcare level in Bangladesh: A qualitative study - Ashraful Kabir; Md Nazmul Karim; Baki Billah (Frontiers in Public Health, 2022)
IntroductionThe weak health system is viewed as a major systematic obstacle to address the rising burden of non-communicable diseases (NCDs) in resource-poor settings. There is little information about the health system challenges and opportunities in organizing NCD services. This study examined the health system challenges and opportunities in organizing NCD services for four major NCDs (cervical cancer, diabetes mellitus, cardiovascular diseases, and chronic respiratory illnesses) at the primary healthcare (PHC) level in Bangladesh.MethodsUsing a qualitative method, data were collected from May to October 2021 by conducting 15 in-depth interviews with local healthcare providers, 14 key informant interviews with facility-based providers and managers, and 16 focus group discussions with community members. Based on a health system dynamics framework, data were analyzed thematically. Information gathered through the methods and sources was triangulated to validate the data.ResultsOrganization of NCD services at the PHC level was influenced by a wide range of health system factors, including the lack of using standard treatment guidelines and protocols, under-regulated informal and profit-based private healthcare sectors, poor health information system and record-keeping, and poor coordination across healthcare providers and platforms. Furthermore, the lack of functional referral services; inadequate medicine, diagnostic facilities, and logistics supply; and a large number of untrained human resources emerged as key weaknesses that affected the organization of NCD services. The availability of NCD-related policy documents, the vast network of healthcare infrastructure and frontline staff, and increased demand for NCD services were identified as the major opportunities.ConclusionDespite the substantial potential, the health system challenge impeded the organization of NCD services delivery at the PHC level. This weakness needs be to addressed to organize quality NCD services to better respond to the rising burden of NCDs at the PHC level.